Influence of Literature Circles Strategy and Cultural Literacy on Students’ English Achievement - Bibie Nariswari; Chuzaimah D. Diem; Machdalena Vianty (Jurnal Bahasa dan Sastra, 2018)
Abstract: This study investigated the influence of Literature Circles Stratey (LCS) and cultural literacy (CL) on 7th and 8th grade students’ English as a foreign language (EFL) achievement of one private junior high school in Palembang, South Sumatera, Indonesia. The students’ EFL achievement was measured by using English tests before and after the three-month intervention using LCS. The results of descriptive statistics showed that although based on paired sample t-test, the students’ EFL achievement increased significantly (mean difference =19.46; p<.000), it was still on below average level. Then, regression analysis also indicated that students’ EFL achievement was inluenced by their CL for 98.00% with reading has the highest percentage. The implication of these results should encourage the eagerness of the in-service teachers of English to apply the strategy appropriately and proportionally to enhance students’ all English skills and researchers to do similar study by involving students of all grade levels of both private and state public schools.  Keywords: EFL learning, literature circles strategy, cultural literacy, junior high school students Abstrak: Penelitian ini meneliti pengaruh Strategi Lingkar Sastra (Literature Circles Strategy – LCS) dan Literasi Budaya (Cultural Literacy – CL) (LCS) pada kemampuan Bahasa Inggris sebagai bahasa asing (EFL) pada siswa kelas 7 dan 8 di sebuah sekolah menengah pertama (SMP) swasta di kota Palembang, Sumatera Selatan, Indonesia. Hasil kemampuan Bahasa Inggris sebagai Bahasa Asing (EFL) diukur dengan menggunakan test Bahasa Inggris sebelum dan sesudah intervensi selama 3 bulan menggunakan LCS.  Hasil dari gambaran statistika menunjukkan bahwa meskipun berdasarkan uji paired sample t-test, hasil kemampuan siswa meningkat secara signifikan (perbedaan nilai rata-rata =19.46; p<.000) masih di bawah angka rata-rata. Kemudian analisis regresi juga menunjukkan bahwa hasil kemampuan Bahasa Inggris sebagai bahwa asing masih dipengaruhi oleh Literasi Budaya 98% dengan presentase tertinggi dalam membaca. Implikasi dari hasil ini seharusnya mendorong kemauan para guru untuk mengaplikasikan strategi ini secara benar dan proporsional untuk meningkatkan semua keterampilan Bahasa Inggris, dan bagi peneliti agar dapat melakukan penelitian serupa dengan melibatkan siswa dari semua tingkat baik sekolah negeri maupun sekolah swasta. Kata-kata kunci: pembelajaran EFL, strategi lingkar sastra, keaksaraan budaya, siswa SMP